Cover Image, Volume 139, Issue 46. Issue 46 (1st November 2022) - Nguyen, Thanh Duong; Schmidt, Thomas; Meißner, Till; Malanin, Mikhail; Uhlig, Kai; Schlendstedt, Kornelia; Schwarz, Simona; Stommel, Markus; Voit, Brigitte; Gedan‐Smolka, Michaela
Abstract : The cover by Thanh‐Duong Nguyen shows the development of novel chemically bonded tribomaterials based on polyamides, irradiated polytetrafluoroethylene, and oil molecules. The materials are formed through a twostep process of reactive‐extrusion. This article presents the compound's morphology, crystallization behavior, and mechanical properties. It was found that PA12‐(Z7321) offered the best coupling degree and is the most suitable matrix polymer for chemical coupling PA‐PTFE‐oil. DOI: 10.1002/app.53012